Teaching English Methods Used in Sekolah Luar Biasa (School for Students with Special Needs) Negeri 2 Singaraja - Kadek Yati Fitria Dewi; Ni Luh Yaniasti (International Journal Labs, 2023)
The choice of teaching method will be largely determined by several factors, one of which is the characteristics of the student. Different characteristics of students require educators to always apply variations in teaching methods. Likewise when teaching students with special needs. Students with special needs can study in public schools (inclusion classes) and some attend special classes, for example in Extraordinary Schools (SLB). This study aims to determine 1) the teaching methods used to teach English for junior and senior high school students at SLB Negeri 2 Singaraja; 2) problems encountered by teachers in teaching English to SP and SMA students at SLB Negeri 2 Singaraja. Data collection was carried out by means of observation, interviews and literature studies (RPP). The data were qualitatively analyzed using the Miles and Huberman model. The output of this research is not only in the form of articles and research reports but also in the form of donations of ideas or ideas related to teaching methods that can be used in teaching English to students with special needs at the junior and senior high school levels. The results showed that 1) the teaching method most often used by English teachers at both the junior and senior high school levels at Sekolah Luar Biasa Negeri 2 Singaraja is a direct method, especially the drilling method; 2) The challenges that teachers often encounter in teaching English are limited focus and memory of students on the subject matter, limitations in receiving and disclosing information and planned materials often not in accordance with student needs when implementing learning.